Ascites affects the benefit of carvedilol on patients with liver cirrhosis and esophageal and gastric varices - Ruiqi Xia; Bing Wu; Ji Zhou; Mingyan Ji; Shuyue Wang; Xiaoqing Zeng; Shiyao Chen (Wiley, 2024)
Abstract Esophageal and gastric varices (EGV) bleeding is a dangerous side effect of liver cirrhosis. Ascites may affect the effectiveness of carvedilol in preventing EGV rebleeding. A retrospective analysis was done on patients with EGV bleeding who visited our gastroenterology department between January 1, 2015, and October 29, 2020, and were given carvedilol therapy again. Patients were classified based on whether they had ascites. The primary outcome was EGV rebleeding. A total of 286 patients were included, with a median follow‐up of 24.0 (19.0-42.0) months, comprising those without ascites (N = 155) and those with ascites (N = 131). The mean age of the patients was 55.15 ± 12.44 years, and 177 (61.9%) of them were men. There were 162 (56.6%) Child‐Pugh A grades. The etiology of cirrhosis included 135 (47.2%) cases of hepatitis B. After carvedilol therapy, the patient's portal vein diameter (DPV) was widened (p < 0.05), velocity of portal vein (VPV) was slowed (p = 0.001). During the 1‐year follow‐up, patients with ascites had a substantially higher rebleeding rate than patients without ascites, with 24 (18.3%) versus 13 (8.4%), respectively (p = 0.013). On univariate analysis, ascites was a risk factor for rebleeding (p = 0.015). The multivariate analysis remained significant after adjusting for age, gender, etiology of cirrhosis, and previous endoscopic treatment, with OR of 2.37 (95% CI: 1.12-5.04; p = 0.025). Ascites was a risk factor for EGV rebleeding in patients undergoing carvedilol therapy. After carvedilol therapy, the patient's DPV was widened and VPV was slowed.